2022
DOI: 10.1057/s41599-022-01340-z
|View full text |Cite
|
Sign up to set email alerts
|

The long-run impacts of paid maternity leave on height and educational attainment

Abstract: This study investigates the extent to which paid maternity leave affects educational attainment and adult height in 29 developing countries between 1990 and 2019. The identification hinges upon the variation in the educational achievement and health outcomes of individuals residing in the same place but exposed to different lengths of paid maternity leave at birth due to policy reforms. The analysis uncovers the long-lasting favorable effects of paid maternity leave as an additional week of leave duration coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…Lucas-Thompson et al ( 183 ) conducted a large meta-analysis of the impact of maternal paid employment on children and found that maternal employment in infancy was associated with reduced scores in formal achievement tests and behavioral problems. Le and Nguyen ( 184 ) used DHS data from 29 countries to explore the impact of increased maternity leave on the height and years of educational attainment of adults born before and after maternity leave improvements. With a sample of nearly 1,000,000 individuals, they found each week increase in paid maternity leave, increased adult height by 0.056 cm and educational attainment by 0.007 years ( 184 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lucas-Thompson et al ( 183 ) conducted a large meta-analysis of the impact of maternal paid employment on children and found that maternal employment in infancy was associated with reduced scores in formal achievement tests and behavioral problems. Le and Nguyen ( 184 ) used DHS data from 29 countries to explore the impact of increased maternity leave on the height and years of educational attainment of adults born before and after maternity leave improvements. With a sample of nearly 1,000,000 individuals, they found each week increase in paid maternity leave, increased adult height by 0.056 cm and educational attainment by 0.007 years ( 184 ).…”
Section: Introductionmentioning
confidence: 99%
“…Le and Nguyen ( 184 ) used DHS data from 29 countries to explore the impact of increased maternity leave on the height and years of educational attainment of adults born before and after maternity leave improvements. With a sample of nearly 1,000,000 individuals, they found each week increase in paid maternity leave, increased adult height by 0.056 cm and educational attainment by 0.007 years ( 184 ). In Norway, a beneficial impact of maternity leave on child development was seen in a 2% decline in high school drop-out rates and 5–7% increase in wages at age 30 for individuals born after paid maternity leave was introduced ( 185 ).…”
Section: Introductionmentioning
confidence: 99%